The international atlas of Mars exploration : the first five decades. Volume 1, 1953 to 2003 - Stooke, Philip J. (Cambridge : Cambridge University Press, 2012)
Covering the first five decades of the exploration of Mars, this atlas is the most detailed visual reference available. It brings together, for the first time, a wealth of information from diverse sources, featuring annotated maps, photographs, tables and detailed descriptions of every Mars mission in chronological order, from the dawn of the space age to Mars Express. Special attention is given to landing site selection, including reference to some missions that were planned but never flew. Phobos and Deimos, the tiny moons of Mars, are covered in a separate section. Contemporary maps reveal our improving knowledge of the planet's surface through the latter half of the twentieth century. Written in non-technical language, this atlas is a unique resource for anyone interested in planetary sciences, the history of space exploration and cartography, while the detailed bibliography and chart data are especially useful for academic researchers and students.
Title from publisher's bibliographic system (viewed on 12 Apr 2018).
Keywords: Mars (Planet) -- Exploration; Mars (Planet) -- Maps; Space flight to Mars -- Maps; Space flight to Mars -- History